Catalyst‐Free π‐Extended Conjugate Addition of Amines to Various Electron‐Deficient π‐Systems. Issue 4 (18th March 2021) - Tan, Minghan; Chrostowski, Robert; Sanematsu, Haruki; Takeuchi, Masayuki; Takai, Atsuro
Abstract: Development of atom‐economical, catalyst‐free, and benign synthetic methods for functionalizing π‐conjugated molecules is of great interest for unconventional organic materials. Here, we report catalyst‐free 1, 6‐ or more π‐extended conjugate addition of amines to ethynyl groups directly attached to various electron‐deficient π‐systems. This hydroamination proceeded quantitatively under mild conditions to afford amino‐functionalized π‐systems. A kinetic study of the reaction revealed that the rate‐determining step was the nucleophilic attack of an amine to the π‐system, and the reaction obeyed typical second‐order kinetics. We found that the hydroamination rates of the π‐systems (the logarithm of the second‐order rate constants) showed a good linear correlation with the chemical shifts of the terminal ethynyl proton in 1 H NMR spectrum. On the basis of the kinetic study of these π‐systems, an asymmetric amine monoadduct could be obtained from the corresponding two ethynyl‐substituted π‐system in a designed manner, and the other ethynyl group could be functionalized through different reactions such as Glaser coupling reaction. Some of the resultant amino‐functionalized π‐systems exhibited characteristic near‐IR emission, and the emission wavelength can be switched reversibly in response to a Brønsted acid and a base. Abstract : Catalyst‐free 1, 6‐ or more π‐extended conjugate addition of amines to ethynyl groups directly attached to various electron‐deficient π‐systems was reported. The hydroamination proceeded quantitatively under mild conditions to afford amino‐functionalized π‐systems.